Swyer syndrome presenting as primary infertility - Chauhan, Nidhi; Bhargava, Surbhi; Anand, Manpreet (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Swyer syndrome was first described by Jim Swyer in 1955. It is a form of “Pure gonadal dysgenesis”. The affected female has 46, XY karyotype. A 21 year old married female came with complaints of primary infertility. On examination she has normal built with normal secondary sexual characteristics. She had normal vaginal opening with small uterus. Serum FSH was 71.54 mIU/ml. Thyroid and Prolactin was in normal range. Karyotype showed genotype of 46, XY. Diagnostic laparoscopy showed streak gonads, small uterus, and normal patent fallopian tubes. Diagnosis of Swyer syndrome was made.